2018
DOI: 10.1074/jbc.ra118.002038
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate remodels apolipoprotein A-I amyloid fibrils into soluble oligomers in the presence of heparin

Abstract: Amyloid deposits of WT apolipoprotein A-I (apoA-I), the main protein component of high-density lipoprotein, accumulate in atherosclerotic plaques where they may contribute to coronary artery disease by increasing plaque burden and instability. Using CD analysis, solid-state NMR spectroscopy, and transmission EM, we report here a surprising cooperative effect of heparin and the green tea polyphenol (−)-epigallocatechin-3-gallate (EGCG), a known inhibitor and modulator of amyloid formation, on apoA-I fibrils. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…An alternative explanation that EGCG prevents fibrils from adhering to the EM grid is unlikely because the disappearance of fibrils becomes gradually pronounced over time in spite of all other variables remaining unchanged, and also because others report that EGCG disaggregates fibrils of other amyloids, including α-synuclein, amyloid β, and apolipoprotein A-I. 12,15 The effect of EGCG treatment on AD-tau could differ from recombinant tau fibrils since recombinant fibrils of tau form different polymorphs. To test whether EGCG disaggregates brain-purified AD-tau fibrils, we examined negatively stained EM grids of purified AD-tau at various times following incubation with EGCG.…”
Section: Egcg Disaggregates Tau By Stoichiometric Binding To Fibrilsmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative explanation that EGCG prevents fibrils from adhering to the EM grid is unlikely because the disappearance of fibrils becomes gradually pronounced over time in spite of all other variables remaining unchanged, and also because others report that EGCG disaggregates fibrils of other amyloids, including α-synuclein, amyloid β, and apolipoprotein A-I. 12,15 The effect of EGCG treatment on AD-tau could differ from recombinant tau fibrils since recombinant fibrils of tau form different polymorphs. To test whether EGCG disaggregates brain-purified AD-tau fibrils, we examined negatively stained EM grids of purified AD-tau at various times following incubation with EGCG.…”
Section: Egcg Disaggregates Tau By Stoichiometric Binding To Fibrilsmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG), a small molecule natural product in green tea, inhibits aggregation of numerous amyloid proteins and, despite their tremendous stability, disaggregates fibrils of some amyloids into smaller units. [11][12][13][14][15] Evidence suggesting that EGCG disaggregates fibrils of tau includes studies in primary rat neurons showing that EGCG enhances clearance of phosphorylated tau, 16 although the reported effects of EGCG are somewhat pleiotropic and range from the inhibition aggregation to altered post-translational modification. 17,18 Here, we sought to illuminate the effects direct binding of EGCG to AD-tau by single-particle cryoEM structure determination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigallocatechin-3-gallate (EGCG), the main polyphenol found in green tea, has been reported to effectively inhibit the aggregation of a number of amyloidogenic peptides and proteins, including amyloid-β (related to AD) [32,33], α-synuclein (related to PD) [33][34][35][36], islet amyloid polypeptide (related to type-II diabetes) [37,38], huntingtin exon 1 (related to Huntington's disease) [39], tau (related to AD and tauopathies) [40], superoxide dismutase (related to amyotrophic lateral sclerosis) [41], prion proteins (related to prion diseases) [42], and others. In addition, it has been shown that EGCG can induce remodeling and/or dissociation of pre-existing aggregate species [33,34,36,43,44]. Taken together, EGCG appears to be a "universal" inhibitor of amyloid fibril formation, suggesting that this molecule could be used as a therapeutic agent for the prevention and treatment of amyloid-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8 In this context, much research has been carried out into the inhibition of amyloidosis by natural aromatic compounds, [16][17][18][19][20][21][22][23][24] including polyphenols from dietary substances that recognise the generic amyloid cross-β motif and alter the aggregation kinetics or restructure many amyloidogenic proteins into non-toxic species in vitro. [22][23][24][25][26] For example, the phenolic rings of polyphenol compounds interfere with the stacking of aromatic residues and hydroxyl groups, thereby destabilising the amyloid core and increasing its solubility. [27][28][29] A common first step toward identifying potential inhibitors is in vitro screening of compounds that reduce tau or Aβ self-assembly kinetics and yield.…”
Section: Introductionmentioning
confidence: 99%